(untitled) (International Journal of Innovative Technologies in Economy, 2024)
South Africa adopted tourism policies that advocate the active participation and involvement of local communities in ecotourism initiatives to improve sustainable livelihoods. This study investigated the contribution of ecotourism initiatives to improved livelihood of UMkhanyakude District Municipality. Eight (8) participants each from four local municipalities, making a total of 32 were purposively interviewed. Data from the participants were processed through the ATLAS TI application. The results revealed that ecotourism contributes to improved livelihood and has also put pressure on community assets such as land, wildlife and cultural practices. The study concludes that despite the prevailing challenges, opportunities exist regarding improvement in the implementation of ecotourism projects and the beneficiation of local communities. The study recommends that ecotourism policy practice at local government level be focused on local communities rather than economy and the tourism industry’s commercial sector.